Synthesis, Crystal Structures and Antimicrobial Activities of 3-bromo-N’-(5-bromo-2- hydroxy-3-methoxybenzylidene)benzohydrazide Monohydrate and 3-Bromo-N’- (4-hydroxy-3-methoxybenzylidene)benzohydrazide monohydrate - Zhu, Hai-Yun (Asian Journal of Chemistry, 2011)
Two new hydrazone compounds, 3-bromo-N'-(5-bromo-2-hydroxy-3-methoxybenzylidene)- benzohydrazide monohydrate (1) and 3-bromo-N'-(4-hydroxy-3-methoxybenzylidene)- benzohydrazide monohydrate (2), have been synthesized and characterized by elemental analysis, IR and single crystal X-ray diffractions. Each compound contains a hydrazone molecule and a water molecule of crystallization. In the crystal structure of (1), molecules are linked through OH ···O hydrogen bonds, forming 2D layers parallel to the ab plane. In the crystal structure of (2), molecules are linked through N-H···O, O-H···O and O-H···N hydrogen bonds, forming 2D layers parallel to the bc plane. The preliminary antimicrobial activities of the compounds were studied.